2015
DOI: 10.1016/j.dcn.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of the uncinate fasciculus: Implications for theory and developmental disorders

Abstract: The uncinate fasciculus (UF) is a long-range white matter tract that connects limbic regions in the temporal lobe to the frontal lobe. The UF is one of the latest developing tracts, and continues maturing into the third decade of life. As such, individual differences in the maturational profile of the UF may serve to explain differences in behavior. Indeed, atypical macrostructure and microstructure of the UF have been reported in numerous studies of individuals with developmental and psychiatric disorders suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
159
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(174 citation statements)
references
References 149 publications
7
159
1
Order By: Relevance
“…At this point, we might only speculate about relationships between tremor symptoms and WM clusters located in UF, ILF, and IFOF. All these bundles are involved in memory retrieval, reward processing, emotional regulation, impulsive responding, semantic language processing, attention, and reversal learning (Mandonnet, Nouet, Gatignol, Capelle, & Duffau, 2007; Martino & De Lucas, 2014; Olson, Von Der Heide, Alm, & Vyas, 2015), although orbitofrontal WM, part of both UF and ILF, was associated with the FTM score (Klein et al., 2011) and showed affected in previous ET study (Shin et al., 2008). Also, atrophy in frontal and temporal gray matter regions, which are interconnected by UF, was found related to the FTM scale (Bagepally et al., 2012) and an improvement of WM integrity within the ILF and IFOF was consistently reported among longitudinal DTI studies evaluating effects of physical training (Huang, Lu, Song, & Wang, 2015; Scholz et al., 2009), implying their involvement in motor functions.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, we might only speculate about relationships between tremor symptoms and WM clusters located in UF, ILF, and IFOF. All these bundles are involved in memory retrieval, reward processing, emotional regulation, impulsive responding, semantic language processing, attention, and reversal learning (Mandonnet, Nouet, Gatignol, Capelle, & Duffau, 2007; Martino & De Lucas, 2014; Olson, Von Der Heide, Alm, & Vyas, 2015), although orbitofrontal WM, part of both UF and ILF, was associated with the FTM score (Klein et al., 2011) and showed affected in previous ET study (Shin et al., 2008). Also, atrophy in frontal and temporal gray matter regions, which are interconnected by UF, was found related to the FTM scale (Bagepally et al., 2012) and an improvement of WM integrity within the ILF and IFOF was consistently reported among longitudinal DTI studies evaluating effects of physical training (Huang, Lu, Song, & Wang, 2015; Scholz et al., 2009), implying their involvement in motor functions.…”
Section: Discussionmentioning
confidence: 99%
“…The uncinate fasciculus connects polar temporal areas, including the amygdala and hippocampus, to cortical regions such as orbitofrontal cortex (OFC) (Kier et al, 2004;Olson et al, 2015;Von der Heide et al, 2013). It therefore connects basic emotion processing areas with regions involved in higher order processing, including emotion regulation.…”
Section: Potential Neural Correlates Of Socio-affective Deficits In Amentioning
confidence: 99%
“…Here, a negative relationship was found between children's self-reported depressive symptoms and FA. The UNC is the main tract connecting the prefrontal cortex with limbic structures including the amygdala and hippocampus (Catani, Howard, Pajevic, & Jones, 2002) and is thought to support emotion regulation, reversal learning, long-term memory retrieval and reward processing (Olson et al, 2015). All of these have been found to function atypically in patients with MDD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While Huang et al (2011) did not find correlations with symptoms, other studies have found associations between FA in the uncinate and trait anxiety in healthy individuals (Kim & Whalen, 2009;Montag, Reuter, Weber, Markett, & Schoene-Bake, 2012); thus it is not clear whether lower FA precedes symptom onset or simply reflects symptom severity. Although the function of the uncinate is still largely unknown several previous studies have implicated its role in reversal learning, reward processing and long-term memory retrieval (Olson et al, 2015). The latter two are often impaired in MDD suggesting that white matter microstructure in the uncinate may be altered.…”
Section: Grey and White Matter Exhibit Differential Developmental Patmentioning
confidence: 99%
See 1 more Smart Citation